(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Corrosion–fatigue of high-strength aluminium alloys is governed not only by reductions in mean fatigue life but, more critically, by systematic changes in fatigue-life dispersion that directly affect structural reliability. In this study, the corrosion–fatigue behaviour of AA 7075-T651 under multiaxial loading is analysed from a dispersion-centred statistical perspective using a Weibull-based framework to quantify how variability evolves with stress level, corrosion exposure, and loading mode. Fatigue data obtained under uncorroded conditions and after 7-day and 14-day NaCl exposure were analysed for bending and torsional loading. Stress-level binning was employed to ensure statistically robust parameter estimation without extrapolation beyond the experimentally tested domain. Rather than treating scatter as experimental noise, the Weibull shape parameter is explicitly interpreted as a stress- and environment-dependent descriptor of fatigue-life variability. The results show that, under uncorroded conditions, fatigue-life dispersion increases significantly at lower stress levels for both bending and torsional loading, consistent with a transition toward initiation-controlled failure. Corrosion exposure produces a pronounced and persistent reduction in the Weibull shape parameter, indicating a fundamental broadening of the fatigue-life distribution that intensifies with increasing exposure duration. Loading mode is further shown to modulate this behaviour, with torsional loading exhibiting distinct dispersion characteristics relative to bending, particularly in corrosive environments. These findings demonstrate that fatigue-life dispersion in AA 7075-T651 cannot be characterised using stress-independent statistical parameters or inferred reliably from mean-life trends alone. Instead, dispersion evolves systematically with stress level, environmental degradation, and loading mode, necessitating stress- and environment-dependent probabilistic descriptions. By explicitly quantifying these effects, the present study provides a statistical basis for advancing corrosion–fatigue assessment beyond conventional deterministic and mean-life-based approaches toward reliability-oriented evaluation under multiaxial loading.